FOLLOW-UP STUDY OF CHILDREN VACCINATED AGAINST HAEMOPHILUS INFLUENZAE TYPE b - A.G. Gaivoronskaya; V.V. Botvin'eva (Union of pediatricians of Russia, 2010)
The article illustrates results from a follow-up study of children vaccinated against Haemophilus influenzae type b. It demonstrates that one year after vaccination children's health condition remains stable. It proves that there is a substantial reduction in acute respiratory infection episodes in the group of children suffered recurrent respiratory infections VS the prior year. It demonstrates that in a follow-up period the protective antibody level remains the same in most children.Key words: Haemophilus influenzae type b, vaccination, children. (Pediatric Pharmacology. - 2010; 7(3):18-21)